PENGELOLAAN SAMPAH ANORGANIK MENJADI BBM MELALUI METODE PIROLISIS DI DESA BEREKAH, KECAMATAN BOJONGGENTENG, KABUPATEN SUKABUMI - Santi Legianti Sutandi (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service through Student Field Work Activities (KKM) is one form of student contribution in addressing issues in the community. This study aims to examine the role of KKM in raising environmental awareness and providing education to the community in Berekah Village, Bojonggenteng District, Sukabumi Regency. This study uses the observation method. KKM students participated in environmental cleanup activities and provided education on the importance of environmental conservation. Our research has shown that the community is starting to understand the significance of maintaining hygiene and caring for their surroundings.